EFEKTIVITAS KONSENTRASI SALINITAS TERHADAP PROFIL PERTUMBUHAN BAKTERI Bacillus cereus strain IMB 11 DALAM MENDEGREDASI BAHAN BAKAR BIOSOLAR - Siti Fatimah; Irda Sayuti; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the effectiveness of salinity concentration on the growth profile of Bacillus cereus strain IMB-11 in degrading biodiesel fuel. This type of research was carried out using the experimental method of the effectiveness of salinity concentration on the growth profile of Bacillus cereus strain IMB-11 in degrading biodiesel fuel. This research was carried out at the Microbiology Laboratory, Faculty of Medicine, University of Riau in December 2022 - January 2023. The data collection method used was visual observation of the growth of Bacillus cereus strain IMB-11 and the number of colonies. Results The results of the study in stage 1, the most effective bacterial growth occurred on the 3rd day, where in treatment 2 a salinity concentration of 2.5 ppm gave a more effective growth of the growth profile of the Bacillus cereus strain IMB-11 in degrading biodiesel fuel in the amount of total colonies 131x106 CFU/mL, followed by the 3rd treatment with a concentration of 5 ppm salinity with a total colony of 96 x 106 CFU/mL, treatment 4 with a concentration of 7.5 ppm salinity with a total colony of 48 x 106 CFU/mL, treatment 5 salinity concentration of 10 ppm with a colony count of 48 x 106 CFU/mL. The conclusion obtained from the study is the effectiveness of a salinity concentration of 2.5 ppm providing more effective growth on the growth profile of the bacteria Bacillus cereus strain IMB-11 in degrading biodiesel fuel with a total number of colonies of 131x106 CFU/mL.Key Words: Salinity, Degradation, Biosolar